Integrated Disease Management, Combining Chemical and Bio-control Agents, is Effective Against Agroathelia rolfsii Infecting Eggplants - Ndifon, Elias Mjaika (International Journal on Food, Agriculture and Natural Resources, 2024)
The seeds of Guibourtia coleosperma serve as potential Agroathelia rolfsii severely infects 500 plant species causing stem and root rots on plants including eggplants. This study evaluated the compatibility of integration of chemical fungicides x biological agents for the management of recalcitrant disease agents like A. rolfsii.  A factorial trial was set up using the completely randomized design with each treatment being replicated thrice. Interaction of Mancozeb (at 50 and 100% concentrations) x Trichoderma species caused 29.3-100% inhibition of A. rolfsii and Ketoconazole (at 50 and 100% concentrations) x Trichoderma species caused 95.8-100% inhibition of A. rolfsii. Mancozeb (100% concentration) x T. harzianum controlled the pathogen most, followed by the T. viride combination. The percentage inhibition by chemical fungicide (main effects) ranged from 100% inhibition by Ketoconazole (100% concentration) to 97.9-100% for Ketoconazole (50% concentration), to 65.2-93.6% for Mancozeb (100% concentration) and lastly 23.3-78.6% for Mancozeb (50% concentration) with time. The percentage inhibition (main effects) ranged from 60.3-96.7% for T. virens, 60.8-92.1% for T. harzianum, and 69.3-95.8% for T. viride with time. The chemical fungicides and Trichoderma species were highly positively correlated (0.522** at p ≤ 0.05). The high concentrations of the fungicides antagonized the Trichoderma species as well, so more work should be carried out on this aspect. This approach to disease management for eggplants is highly effective using chemical x bio-control agents to safeguard eggplants from A. rolfsii. Applying this method can protect crops and result in long-term profitability. The combination of fungicides and biocontrol agents is strongly recommended for the management of this fungal pathogen.